2017
DOI: 10.1128/aac.02122-16
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Component System ChtRS Contributes to Chlorhexidine Tolerance in Enterococcus faecium

Abstract: Enterococcus faecium is one of the primary causes of nosocomial infections. Disinfectants are commonly used to prevent infections with multidrugresistant E. faecium in hospitals. Worryingly, E. faecium strains that exhibit tolerance to disinfectants have already been described. We aimed to identify and characterize E. faecium genes that contribute to tolerance to the disinfectant chlorhexidine (CHX). We used a transposon mutant library, constructed in a multidrug-resistant E. faecium bloodstream isolate, to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 60 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Earlier studies with other oral streptococci, including Streptococcus sanguinis and Streptococcus mitis, showed that repeated exposure to CHX resulted in increased MICs to CHX, but these findings were not deemed to be of clinical significance (13)(14)(15)(16)(17). In enterococci, increased tolerance to antiseptics such as CHX in hospital settings has inspired research into the mechanisms for increased CHX tolerance, including studies of CHX effects on the transcriptome (18) and analysis of the impact of CHX on a transposon mutant library (19). More specifically, Bhardwaj and colleagues (18) used transcriptome sequencing (RNA-Seq) to show that VanA-type vancomycin resistance genes are upregulated in Enterococcus faecium following exposure to CHX.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies with other oral streptococci, including Streptococcus sanguinis and Streptococcus mitis, showed that repeated exposure to CHX resulted in increased MICs to CHX, but these findings were not deemed to be of clinical significance (13)(14)(15)(16)(17). In enterococci, increased tolerance to antiseptics such as CHX in hospital settings has inspired research into the mechanisms for increased CHX tolerance, including studies of CHX effects on the transcriptome (18) and analysis of the impact of CHX on a transposon mutant library (19). More specifically, Bhardwaj and colleagues (18) used transcriptome sequencing (RNA-Seq) to show that VanA-type vancomycin resistance genes are upregulated in Enterococcus faecium following exposure to CHX.…”
mentioning
confidence: 99%
“…More specifically, Bhardwaj and colleagues (18) used transcriptome sequencing (RNA-Seq) to show that VanA-type vancomycin resistance genes are upregulated in Enterococcus faecium following exposure to CHX. In E. faecium, two genes encoding a two-component regulatory system were found to contribute to CHX tolerance (19). Thus, it is clear that Firmicutes have the capacity to develop increased tolerance to CHX, but the mechanisms by which tolerance may develop, especially in streptococci, are only beginning to be explored.…”
mentioning
confidence: 99%
“…The two main mechanisms include CHX efflux (23, 42-44, 64-67) and changes in outer membrane content (68, 69). The recently identified two-component system ChtRS contributes to CHX tolerance in E. faecium , presumably via regulation of expression of genes in its regulon, which is currently undefined (70). In this study, we have confirmed a role for the heterodimeric ABC transporter in CHX susceptibility in VREfm.…”
Section: Discussionmentioning
confidence: 99%
“…However one recent study (6) reported that when CHX was continuously flowed on biofilms formed on polystyrene blocks in vitro, detached cells displayed a higher minimal inhibitory concentration (MIC) to CHX (1.25 μg mL −1 ), whereas most isolates of S. mutans evaluated had MICs < 1μg mL 1 . In enterococci, increased tolerance to antiseptics such as CHX in the hospital setting has inspired research into methods of increased CHX tolerance, including studies of CHX effects on the transcriptome (11) and on a transposon mutant library (12). More specifically, Bhardwaj and colleagues (11) used RNA-Seq to show that VanA-type vancomycin resistance genes are upregulated in Enterococcus faecium following CHX exposure.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Bhardwaj and colleagues (11) used RNA-Seq to show that VanA-type vancomycin resistance genes are upregulated in Enterococcus faecium following CHX exposure. In E. faecium, two genes encoding for a two-component regulatory system were found to contribute to CHX tolerance (12). Thus, it is clear that Firmicutes have the capacity to develop increased tolerance to CHX, however the mechanisms by which tolerance may develop, especially in streptococci, is only beginning to be explored.…”
Section: Introductionmentioning
confidence: 99%